"Fear of Falling": Economic Instability Enhances Collective Angst among Societies' Wealthy Class. (March 2017) - Jetten, Jolanda; Mols, Frank; Healy, Nikita; Spears, Russell
Abstract : In 2008, an era of unprecedented growth and prosperity came to an end, and the world was plunged into the Great Recession, a Global Financial Crisis (GFC)—the worst since the 1930s Great Depression. We examined whether it is low‐ or high‐SES people that are most affected psychologically—and most likely to express concern about the future vitality of their group—by uncertainty associated with economic instability. In two experiments, we found that even though those lower in SES report more collective angst than their wealthier counterparts, those who are higher in SES are more likely to become concerned when presented with information that the economy is a bubble about to burst, elevating their collective angst levels. Both studies also showed that collective self‐definitions as competent and warm were affected by wealth but not by economic instability. Competence ratings increased with increasing wealth, whereas warmth ratings were lower for those both lower and higher in wealth, compared to those with moderate wealth. In Experiment 2, we also found that opposition to immigration was higher for the high‐income group in the unstable than in the stable economic prospect condition. We conclude that even though those lower in income experience chronic collective angst, collective angst levels for those higher in income are elevated when they fear they may be living in a bubble economy—a bubble that may burst any moment.